Evaluation of Heavy Metal Contamination Ecological Risk in a Food-Producing Ecosystem - mohsen Mirzaei; Safar Marofi; eisa Solgi; Mozhgan Abbasi; Roohollah Karimi (Mazandaran University of Medical Sciences, 2017)
Introduction and purpose: The consumption of agricultural products cultivated in soils contaminated with heavy metals is very health-threatening. Therefore, the implementation of an inclusive and multilateral assessment of the heavy metal risk on the verge of their entrance to the food chain is a matter of fundamental importance. Regarding this, the present study was conducted with the aim of monitoring the concentration of heavy metals in the surface soil of grape gardens and zoning the area in terms of geoaccumulation index (Igeo), contamination factor, degree of contamination, modified degree of contamination (MDC), pollution load index (PLI), and ecological risk index (RI). Methods: For the purpose of the study, 31 grape gardens were selected in Gahru region (i.e., the main center of grape production) through simple random sampling technique. The surface soil samples were transferred to the laboratory for the analysis of the concentration of cadmium, lead, chromium, copper, and zinc. Results: According to the results, the concentration of the metals in the region was Zn > Cu > Pb > Cr > Cd with the mean total concentrations of 74.87, 55.31, 22.32, 9.81, and 0.91 mg/kg, respectively. Based on the results of the PLI, six grape gardens were classified as insignificantly contaminated (1≤PLI≤2), and the remaining gardens were classified as noncontaminated (PLI<1). In additon, the results of the RI revealed that 3, 4, and 24 gape gardens had significant (RI>300), medium (150<riConclusion: In the present study, the Igeo and MDC had higher efficiency and flexibility in the classification of the area in terms of critical metals and critical stations. Meanwhile, cadmium and copper caused the highest concern in some of the grape gardens of the investigated region. Therefore, it is suggested to prevent the entrance of larger amounts of cadmium in the area by training and raising the awareness of the gardeners about the amount of phosphate fertilizers and fungicide and encouraging them to use animal manures and take preventive measures. In addition, the cadmium contamination in the area should be reduced by implementing a soil refinery program and cultivating cadmium adsorbents.</ri